2015
DOI: 10.1007/s13762-015-0898-7
|View full text |Cite
|
Sign up to set email alerts
|

An overview of particulate dry deposition: measuring methods, deposition velocity and controlling factors

Abstract: Much importance was given to dry deposition over the past few decades as it deteriorated the environmental conditions and resulted in subsequent health effects. This paper starts with an overall scenario of dry deposition research; it focuses on: various particulate dry deposition flux measurement methods, comparison of various published numerical values on dry deposition velocity and factors controlling dry deposition velocity. This work provides a technical overview to research studies on the current state o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…Sensitive to ambient environmental factors, such as light and water status, the stomas can open to different extent, and thus lead to different rates of transpiration which in turn alters relative humidity. Given that relative humidity influences dry deposition velocity, foliar accumulation of PM 2.5 capture could be impacted 66 . Although the particles have been observed to enter the leaf through stomatal openings 67 , the frequency to which this occurs is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitive to ambient environmental factors, such as light and water status, the stomas can open to different extent, and thus lead to different rates of transpiration which in turn alters relative humidity. Given that relative humidity influences dry deposition velocity, foliar accumulation of PM 2.5 capture could be impacted 66 . Although the particles have been observed to enter the leaf through stomatal openings 67 , the frequency to which this occurs is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…At monitoring sites for atmospheric deposition studies, wet deposition is typically monitored through the collection of precipitation and subsequent laboratory analysis of precipitation composition (Amodio et al, 2014). Directly measuring dry deposition is expensive and technically challenging (Mohan, 2016;Wright et al, 2016); thus, ambient concentrations of pollutants of interest are measured for subsequent dry deposition estimation using the inferential method (e.g., Ban et al, 2016;Baumgardner et al, 2002;Flechard et al, 2011;Zhang et al, 2016). However, in chemical transport models (CTMs), both dry and wet deposition processes are parameterized and are mostly semiempirical or empirical algorithms (Gong et al, 2011;Pleim & Ran, 2011;Vivanco et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, dry deposition estimates for these species still have large uncertainties due to the many chemical, biological, and meteorological factors affecting dry deposition processes. Uncertainties for other chemical species are even larger (Fowler et al, 2009;Hicks et al, 2016;Mohan, 2016;Wesely & Hicks, 2000;Wright et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports indicate detection in the air (Schlichting, 1969) and in precipitation (Cáliz et al, 2018). Trebouxiophyceae is also found in seawater (Tragin and Vaulot, 2018) and might therefore also be dispersed in the form of sea spray from aqueous ecosystems (Tesson et al, 2016;Mayol et al, 2014). Cáliz et al (2018) reported enrichment in rainfall at sample sites where aerosols of marine origin were dominant.…”
Section: Discussionmentioning
confidence: 93%